PEMBINAAN PENULISAN GRAFITI SEBAGAI WADAH CREATIVE ENTREPRENEUR BERBASIS KEARIFAN LOKAL BUDAYA MELAYU DELI - Juliana Juliana; Fatimah Fatimah; Apriliyanti Apriliyanti (Jurnal Lingua Idea, 2018)
In reality graffiti writings sometimes create some problems to the beauty of the environment. One of the problems are the creation of graffiti writings by Me&an art community on the streetwalls that affect the cleanliness of urban. Therefore, it is needed for a media as a place for the Me&an art community to express their creativity. The objective of this study is to give solution for the problem by providing a development media of graffiti writings for Me&an art community to become creative entrepreneur based on local wisdom of Malay Deli. This study focuses on developing graffiti writings by using and applying local wisdom values of Malay Deli. The results of this study are the sourvenirs model and the development place of graffiti writing as a media to express creativity based on local wisdom of Malay Deli. Briefly, the model of graffiti writing based on Malay Deli as a development media for Me&an art community to become creative industry entrepreneurs based the local wisdom.